The people have never stopped dancing : Native American modern dance histories - Shea Murphy, Jacqueline, 1964- (University of Minnesota Press, 2007)
In this first major study of contemporary Native American dance, Jacqueline Shea Murphy shows how these concert performances are at once diverse and connected by common influences. Illustrating how Native dance enacts cultural connections to land, ancestors, and animals, as well as spiritual and political concerns, Shea Murphy challenges stereotypes and offers new ways of recognizing the agency of bodies on stage.